Relative fractional dynamics of stock markets - Machado, J.A.Tenreiro (2016)
This paper analyses motion of stock markets (SM) in the perspective of fractional calculus and introduces the concept of relative fractional dynamics. The SM are characterized by long-range correlations and persistent memory. These features are found in natural and artificial systems and are well modelled by means of the tools of fractional calculus.The time series of daily closing prices of 11 SM for the period 9 July 1987 to 22 April 2016 are interpreted as motion trajectories and their distances analysed through the Fourier transform. The amplitude spectra are approximated by power lawfunctions, characterizing the relative motion of the financial indices and their slow tendency to synchronize.